PENGARUH PRODUK DAN HARGA AKOMODASI TERHADAP MINAT WISATAWAN MENGINAP DI KOTA BUKITTINGGI - Wina Asty; Vina Kumala; Dewi Angraini (Ensiklopedia Social Review, 2021)
In the last three years, it has been seen that the level of tourist visits in the City of Bukittinggi has increased significantly. Business actors and the government are also racing to improve tourism infrastructure, including lodging facilities. Based on observations, data was obtained that in 2018 the number of accommodations in the City of Bukittinggi was 107 inns. The number of guests staying in 2016-2017 increased by 1.51%, then in 2017-2018, it increased by 5.66%. This study aims to examine the effect of products and accommodation prices on the purchase interest of tourists in the city of Buktinggi using quantitative descriptive methods. The population used is tourists who have stayed at the accommodation in the city of Bukittinggi, with a sample size of 100 respondents. Primary data was obtained through distributing questionnaires, and secondary data was obtained from the Department of Tourism, Youth, and Sports, by testing the hypothesis of multiple linear regression techniques. The results showed that the products offered affected the purchase interest of tourists, while the price of accommodation did not affect the interest of tourists to stay in the city of Bukittinggi.